Plastic Fantastic: Schwann Cells and Repair of the Peripheral Nervous System. (1st July 2013) - Kim, Haesun A.; Mindos, Thomas; Parkinson, David B.
Abstract : Repair in the peripheral nervous system (PNS) is a complex process that requires the active de‐differentiation of Schwann cells to an immature repair state following injury; this de‐differentiation is dependent upon the activity of the p38 and ERK1/2 mitogen‐activated protein kinases, as well as the transcription factor cJun. Understanding the mechanisms of repair raises the possibility of both boosting repair after PNS trauma and even, possibly, blocking the inappropriate demyelination seen in some disorders of the peripheral nervous system. Abstract : Summary: Repair in the peripheral nervous system (PNS) depends upon the plasticity of the myelinating cells, Schwann cells, and their ability to dedifferentiate, direct axonal regrowth, remyelinate, and allow functional recovery. The ability of such an exquisitely specialized myelinating cell to revert to an immature dedifferentiated cell that can direct repair is remarkable, making Schwann cells one of the very few regenerative cell types in our bodies. However, the idea that the PNS always repairs after injury, in contrast to the central nervous system, is not true. Repair in patients after nerve trauma can be incredibly variable, depending on the site and type of injury, and only a relatively small number of axons may fully regrow and reinnervate their targets. Recent research has shown that it is an active process that drives Schwann cells back to an immature state after injury and that this requires activity of the p38 and extracellular‐regulated kinase 1/2 mitogen‐activated protein kinases, as well as the transcription factor cJun. Analysis of the events after peripheral nerve transection has shown how signaling from nerve fibroblasts forms Schwann cells into cords in the newly generated nerve bridge, via Sox2 induction, to allow the regenerating axons to cross the gap. Understanding these pathways and identifying additional mechanisms involved in these processes raises the possibility of both boosting repair after PNS trauma and even, possibly, blocking the inappropriate demyelination seen in some disorders of the peripheral nervous system.